Recommendations for the Design of Urban Mobility Applications Based on the Study of the User Experience - Pinheiro, Mateus Pinheiro; Carneiro, Nayana Carneiro; Darin, Ticianne Darin; Keywords, Author Keywords (Teste; 2018: IHC_19, 2019)
The user experience (UX) seeks to understand how people experience interaction with technological artifacts, from various points of view. Through an empirical research of qualitative nature, the present paper explores how interaction and interface problems impact the user experience in mobile applications focused on urban mobility. To support the study, we evaluated the user experience offered by two of these applications, whose evaluation process consisted of a combination of methods, aiming to cover several aspects of the user experience. The evaluation results emphasize the need of concerning about aspects that go beyond the quality of use in mobile application design. Based on our findings, we present recommendations for designing urban mobility mobile applications that offer a satisfying and enjoyable user experience.